Pengaruh Disiplin Kerja, Motivasi Kerja, dan Lingkungan Kerja terhadap Kinerja Karyawan pada Prisma Billiard Kediri - Muhammad Bintang Alkindy Z; Ahmad Jauhari; Beny Mahyudi S (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to analyze the influence of work discipline, work motivation, and work environment on employee performance at Prisma Billiard Kediri. The background of this study is based on the importance of employees' role in determining organizational success, especially in the service sector, which is highly dependent on human resource performance. In addition, inconsistencies were found in the results of previous studies regarding the influence of these variables on employee performance, so further studies are needed. This study uses a quantitative descriptive approach with data collection methods through questionnaires, direct field observations, interviews with relevant parties, and documentation. The sampling technique used a saturated sampling method, namely the entire population of 36 employees was used as the research sample. The data obtained were analyzed using multiple linear regression analysis techniques. The results of the analysis indicate that the variables of work discipline and work environment have a positive and significant influence on employee performance. This means that the higher the level of discipline and the better the work environment, the employee performance tends to increase. Conversely, work motivation in this study showed a negative influence on performance, indicating that the current motivation is not aligned with the goals and expectations of employees. Simultaneously, these three variables were proven to have a significant influence on employee performance. These findings imply that management needs to pay more attention to establishing a culture of discipline and creating a conducive work environment, as well as evaluating approaches to motivating employees.